Avaliação da terapia por fotobiomodulação sobre a atividade dos condrócitos e cartilagem articular em modelo experimental de artrite reumatoide - Fernandes, Guilherme Henrique Cardoso (2021)
Rheumatoid Arthritis (RA) is a chronic inflammatory, autoimmune, systemic and progressive disease that leads to irreversible destruction of cartilage and bone. In vivo and in vitro experimental studies using photobiomodulation therapy have shown positive effects on the modulation of factors that cause disease progression. The objective of this work was to evaluate the effects of photobiomodulation therapy in the treatment of induced Rheumatoid Arthritis (RA) in vitro and in vivo, in relation to cellular, biochemical and functional aspects. Methodology applied in the in vitro step recovered cartilage-derived chondrocytes with induced Rheumatoid Arthritis. Chondrocytes were cultured in 96-well plates, considered healthy chondrocytes (CD) or derived from cartilages with induced RA, untreated (NT) or treated with PBM at different parameters, wavelength 810nm, 2J energy and 35, 50, 100mW of power and cell proliferation was evaluated. In the in vivo step, 25 male Wistar rats were used, divided into groups, CTL (control), RA (Rheumatoid Arthritis) and RA + PBM. For the induction of RA, 3 injections of the lesion-inducing solution (CIA) were used on days 0, 7 and 21 days after the last induction. For groups that received PBM treatment (808nm; 2J; 100mW) irradiation started immediately after the last induction. The strength (Fmax) and maximum deformation (Dmax) supported by the cartilage until the moment of rupture were evaluated. The quantification of the gene expression of MMPs 2, 9 and 13 is performed. Results: The results of the evaluation of cell proliferation showed that the NT group showed a reduction in cell proliferation after 48 hours. The groups irradiated with powers of 35mW and 100mW showed increased cell proliferation. Increased proliferation of RA chondrocytes treated with PBM and reduced Fmax and Dmax were observed in RA groups. PBM reduced the biomechanical changes caused by RA and the expression of MMPs 2,9 and 13, preventing disease progression. Conclusion: PBM promoted an improvement in the functional and biochemical characteristics, reducing the impact on cartilage resistance and reducing the expression of MMPs. The 810nm wavelengths at 2J energy were efficient in increasing cell proliferation and maintaining viability. Suggesting that it is an important therapy in the treatment of rheumatoid arthritis with no known side effects.